Promoting colonoscopy screening among low‐income Latinos at average risk of colorectal cancer: A randomized clinical trial. Issue 4 (19th November 2019) - DuHamel, Katherine N.; Schofield, Elizabeth A.; Villagra, Cristina; Sriphanlop, Pathu; Itzkowitz, Steven H.; Cotter, Gina; Cohen, Noah; Erwin, Deborah O.; Winkel, Gary; Thompson, Hayley S.; Zauber, Ann G.; Jandorf, Lina H.
Abstract : Background: Screening colonoscopy (SC) for colorectal cancer (CRC) is underused by Latino individuals. The current randomized clinical trial examined the impact of 3 interventions: 1) patient navigation; 2) patient navigation plus standard Centers for Disease Control and Prevention print materials; and 3) patient navigation plus culturally targeted print materials for Latinos referred for SC. Demographic, personal and health history, and psychometric factors associated with SC also were examined. Methods: A total of 344 urban Latino individuals aged 50 to 85 years with no personal and/or immediate family history of CRC diagnosed before age 60 years, no personal history of a gastrointestinal disorder, no colonoscopy within the past 5 years, with insurance coverage, and with a referral for SC were consented. Participants were randomized to patient navigation (20%), patient navigation plus standard Centers for Disease Control and Prevention print materials (40%), and patient navigation plus culturally targeted print materials (40%). The completion of SC was assessed at 12 months. Results: The interventions had an overall SC rate of 82%. Counterintuitively, patients with an average income of <10, 000 were found to have higher SC rates (87%) than those with a greater income (75%). Conclusions: The addition of standard or culturally targeted print materials did not appear to increase SC rates above those for patient navigation. Indeed, after controlling for other variables, culturally targeted print materials were found to be associated with lower SC rates among Puerto Rican individuals. Abstract : The results of the current randomized clinical trial indicate that patient navigation leads to high rates of screening colonoscopy among Latino individuals. Adding print materials does not appear to increase screening colonoscopy rates above those of patient navigation alone.